The Relationship Between Digital Technology and Business Innovation Model Among Asnafpreneurs in Malaysia - HARUN, NORAZMAN; AHMAD ROYALI, SURYA; TAMRIN, MASLIANA; MD BADARUDIN, ISMADI; ILYAS, ILYA YASNORIZAR; AHMAD, NOR HALAWAH; MOHD MUNAHAR, MUSLIHAH (Information Management and Business Review, 2024)
Businesses must continually adapt and innovate to stay competitive and maintain high market shares. This includes not only incorporating the latest technology but also creating innovations that aim to increase profitability and sustainability. However, this approach also involves significant risks, as changing the business model to incorporate technological and sustainable elements can be challenging. Digital technology has forced entrepreneurs to reconsider their business models, leading to a need for research on entrepreneurial intention and business models in this area. Thus, this paper seeks to identify the relationship between digital technology and the business innovation model among asnafpreneurs in Malaysia. The study will use a quantitative approach, with a structured survey conducted using Google Forms to gather data. The researcher will use purposive and judgmental sampling, based on recommendations from zakat officers, to select a sample of 299 respondents. Descriptive analysis will be used to examine the existing elements of digital technology, while correlation analysis will be used to examine the relationship between the dependent variable (business innovation model) and the independent variables (digital technology). The study’s objective is to analyze the relationship between the business innovation model with digital technology and to propose the elements of digital technology in business innovation to asnafpreneur.